2013
DOI: 10.12988/asb.2013.3211
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinity effect on carbon isotope composition of plant biomass

Abstract: The analysis of the carbon isotopic data available from the literature evidences in favor of the significant effect of salinity on plant and photosynthesizing alga biomass. The nature of this effect is explained in terms of oscillation model of carbon isotope fractionation in photosynthesis. The data interpretation and conclusions are compared with those obtained from commonly adopted steadystate model of carbon isotope fractionation in photosynthesis. It is shown that the first model gives a new explanation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Natural observations and in vitro experiments showed that the carbon isotopic variations depending on CO 2 concentrations in the environment may achieve 25%o [20]. It was also found [21] that the 12 C enrichment of biomass turned out to be much less than the carbon isotope effects of RuBP carboxylation on the enzymes isolated from the biomass of these organisms. The effects were about 60-65%o.…”
Section: Cmentioning
confidence: 95%
See 3 more Smart Citations
“…Natural observations and in vitro experiments showed that the carbon isotopic variations depending on CO 2 concentrations in the environment may achieve 25%o [20]. It was also found [21] that the 12 C enrichment of biomass turned out to be much less than the carbon isotope effects of RuBP carboxylation on the enzymes isolated from the biomass of these organisms. The effects were about 60-65%o.…”
Section: Cmentioning
confidence: 95%
“…CO 2 assimilation results in enrichment of total biomass in 12 C isotope whereas photorespiration leads to accumulation in biomass of 13 …”
Section: Carbon Isotope Fractionation In Global Photosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Our CID data are in agreement with the salt tolerance of the standard lines and confirmed their classes as tolerant, moderately tolerant and susceptible. For more information on the use CID as a surrogate for salt tolerance, the reader is referred to recent publications [46][47][48]. Here we focus on the ability to screen for salt tolerance using element composition in non-stressed conditions.…”
Section: Validation Experimentsmentioning
confidence: 99%